2015
DOI: 10.1099/ijsem.0.000573
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides caecigallinarum sp. nov., isolated from caecum of an Indonesian chicken

Abstract: Three strains of anaerobic Gram-stain-negative, short to longer rod-shaped bacteria isolated from the caecum of chicken in Indonesia were studied using a polyphasic taxonomic approach. These strains belonged to the genus Bacteroides, based on sequence analysis of 16S rRNA and hsp60 (groEL) genes, with similarities of 93.2-94.1 and 89.8-90.8 %, respectively, to the closest recognized species, Bacteroides coprocola JCM 17929 T . Sugar fermentation and enzyme characteristics, cellular fatty acid profiles, menaqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…Furthermore, Bacteroides was enriched significantly in the BL medium, which indicated that it could be isolated in the BL medium. This result is consistent with other studies, and some novel Bacteroides species were isolated using medium containing blood (Bakir et al 2006a , b ; Kitahara et al 2012 ; Saputra et al 2015 ). Interestingly, 692 unique anaerobic episodes were isolated from the blood cultures in a clinical study, while the Bacteroides spp.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Bacteroides was enriched significantly in the BL medium, which indicated that it could be isolated in the BL medium. This result is consistent with other studies, and some novel Bacteroides species were isolated using medium containing blood (Bakir et al 2006a , b ; Kitahara et al 2012 ; Saputra et al 2015 ). Interestingly, 692 unique anaerobic episodes were isolated from the blood cultures in a clinical study, while the Bacteroides spp.…”
Section: Discussionsupporting
confidence: 92%
“…The description is as for Bacteroides caecigallinarum (Saputra et al, 2015). The type strain is C13EG111 = InaCC B455 = NBRC 110959.…”
Section: Discussionmentioning
confidence: 99%
“…Many Bacteroidetes produce pigments, particularly carotenoids (Goodwin, 1980; Sowmya and Sachindra, 2016) and flexirubin-like pigments (Reichenbach et al, 1974, 1980); in some cases proteorhodopsin has been observed (González et al, 2008; Yoshizawa et al, 2012). The cell shape ranges from short rods to long filaments (Saputra et al, 2015; Hahnke R. L. et al, 2016); longer cells are often flexible, including curved or helical shapes (Eder et al, 2015; Shakeela et al, 2015a). Spherical degenerative forms called “spheroblasts” are known from Flavobacterium (Bernardet and Bowman, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…B. dorei , B. clarus , B. uniformis , B. xylanisolvens , B. ovatus , B. thetaiotaomicron and B. vulgatus represented human-adapted species while B. salanitronis , B. caecigallinarum , M. massiliensis , B. plebeius , B. coprocola , B. caecicola and B. mediterraneensis were specific for chickens. A certain degree of host adaptation could be expected as B. dorei , B. uniformis , B. xylanisolvens and B. ovatus were reported as common to human gut microbiota [ 8 , 9 , 25 , 26 ] and B. plebeius and B. caecigallinarum are common in chickens [ 27 , 28 ]. However, the extent and contrast of the host adaptation was unexpected, since representatives of 12 species were originally isolated from chickens [ 7 ] and B. thetaiotaomicron and B. vulgatus were originally cultured from pig faeces.…”
Section: Discussionmentioning
confidence: 99%